The Design Research of Intelligent Suitcase- - Yongchuan Li (Journal of Digital Information Management, 2017)
By means of advanced mobile internet technology and combining with practical problem in use of suitcase, the smart suitcase is researched and developed to meet users’ demands for safety, carrying and entertainment, so as to provide users’ trip with intelligent solution. Meanwhile, the innovation of core functional units of smart suitcase is proposed to implement intelligent design of traditional suitcase, research suitcase relevant elements repeatedly, improve function, shape, structure, material, technology as well as color, and enhance product quality via design. On the one hand, the topic research refreshes traditional trip mode so that people can experience the convenience of smart trip; on the other hand, it provides people with faster use mode and meets users’ demands for personalized as well as high-tech products. Nowadays, the design of smart products under the era of internet of things has become a new trend, which meets users’ demand for suitcase, enables users to control smart suitcase easily with enjoying the comfort brought by the product, and keeps creating benefits for users and society.